The Effect of E-Servicescape Dimensions on Repurchase Intention with Trust as an Intervening Variable - Rahayu Aprianti; Indira Rachmawati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
This research to determine how much influence the e-servicescape dimension has on repurchase intention through trust as an intervening variable. The object of this study is the food-delivery service on mobile applications, Grab Food. The population used in this study were users of Grab Food services in Indonesia with a sample of 400 respondents who had purchased products through Grab Food in Indonesia obtained using purposive sampling techniques. Samples were obtained from distributing online questionnaires via Google Form. The independent variables used in the study are the e-servicescape dimensions, namely: aesthetic appeal, layout and functionality, and financial security. The dependent variable used in this study is repurchase intention and trust as intervening variables. The data analysis technique used in this research is Structural Equation Modeling with Covariance Based Structural Equation Modeling (CB-SEM). Based on the results of research that has been done, E-servicescape has a positive and significant effect on repurchase intention through trust variables.